Open garbage dumps and knowledge of rabies among sanitary workers - Abedi, Ali Jafar; Khan, Samreen; Mehnaz, Saira; Ansari, M. Athar (International Journal Of Community Medicine And Public Health, 2017)
Background: Rabies is a potentially fatal disease with significant public health importance. Awareness among sanitation workers is a key component for prevention, and needs to be addressed. Therefore, a study was conducted with the objectives to determine the awareness of rabies and role of open garbage dumps in the spread of rabies among sanitary workers. Methods: A cross sectional study was conducted from January to February, 2017. All of the 65 sanitation workers employed by the University Health Office, Aligarh Muslim University, Aligarh were included in the study after taking their verbal consent. A total of 26 Open Garbage Dumps were studied and classified. The knowledge of rabies was assessed by evolving a scoring system. The data were then analyzed using SPSS statistical software version 24.0. Results: The mean age of the study population is 32.93 years (mean 38 years, SD 9.74). 62 (95.4%) were males. Mean duration of work was 8.14 years (SD 7.45). Maximum number of study participants had received education uptil high school and belonged to social class II. Mean knowledge score paired with different socio-demographic variables show a highly significant association with age, sex, duration of work, education, religion, socio-economic status and whether they owned a pet or not. Conclusions: Our study revealed that knowledge regarding OGDs and their role in the spread of rabies is poor. OGDs near residential houses and stray dogs increase the risk factors for canine rabies. Therefore, sustained efforts to decrease the stray dog population in residential areas should be advocated.